PELATIHAN DIGITALISASI MARKETING DALAM UPAYA PENINGKATAN PRODUKSI DAN PEMASARAN PADA BISNIS ONLINE UMKM KERUPUK IKAN KELURAHAN PASIR PANJANG (LPPM Universitas Dinamika Bangsa, 2023)
Abstract Digital Marketing plays an important role for MSME actors in marketing their products so that later it is expected to be able to increase sales. This condition also results in consumer changes in fulfilling lifestyles. In order to continue to increase this contribution and participation, MSMEs are required to be involved in digital platforms. In the midst of difficulties in keeping MSMEs in operation, one of the sectors that has benefited is the sector that uses digital/online services. Through this PKM, MSME actors, in this case the Long Sand Fish Cracker MSME, will be given training that aims to increase knowledge about digital marketing methods. The purpose of the digitalization marketing training is so that MSME actors are more active in promoting their business through digital media which is expected to increase promotion thereby increasing production results. The methods used in this PKM activity are: 1.) provision of material on digitalization of marketing, 2.) provision of material on the use of digital media as a marketing tool, 3.) practice of making digital online media. Kata kunci: MSMEs, Marketing Digitalization, Online Marketing